The evolution of health policy and systems research in 11 low- and middle-income countries and the role of the Alliance for Health Policy and Systems Research: a bibliometric analysis for 1999–2020 - Nino Paichadze; Emma K. Cook; Heather E. Rosen; Sara Kurtovic; Adnan A. Hyder (Health Research Policy and Systems)
Abstract Objectives Given the rapid growth of the field of health policy and systems research (HPSR), it is important to monitor the research environment, especially the evolution of HPSR research outputs in low- and middle-income countries (LMICs). The objective of this study was to generate quantitative metrics to assess the production of HPSR publications and the role of the Alliance for Health Policy and Systems Research (the Alliance) grant-funded projects in 11 LMICs over the past 20 years. Methods We conducted a systematic literature search for HPSR literature from 1999 to 2020 pertaining to 11 target LMIC countries, including grey literature. We analysed the frequency of publications over time, by country and by thematic area. We then used a database of the Alliance’s previous grantees to analyse authorship by Alliance-funded investigators. Results HPSR publications across all 11 target countries increased steadily over the past two decades and the rate of publication increased by an average of 34% per year. The majority of HPSR publications during the study period were in health systems (23%) and health workforce (19%) thematic areas. Nineteen per cent of HPSR publications during this time were authored by Alliance-funded investigators. There was extensive heterogeneity between countries both in number of publications and in proportion of publications authored by Alliance-funded investigators. Conclusions Growth in the HPSR research environment reflects the expanding prominence of the HPSR field and increased HPSR research capacity in the 11 target countries. Alliance-funded investigators made an important contribution to the growth in HPSR output in these countries.